Vulnerabilidade de formigas do Cerrado ao aquecimento global: influência de características morfológicas, comportamentais e ecológicas - Zuanon, Lino Abdelnour (2023)
Global warming is one of the biggest threats to biodiversity conservation. Although the rate of warming is higher at higher latitudes, it is the tropical ectothermic organisms that are the most risk . In this sense, it is urgent to understand more about the thermal biology of these organisms. In my study I explored some of the ecological and behavioral factors that may help explain the thermal tolerance and vulnerability to global warming of Neotropical savanna (Cerrado) ants. Firstly, I sought to understand the extent to which the type of habitat and nesting/foraging stratum help to explain the thermal tolerance and vulnerability to global warming of these ants. For this, I measured the thermal tolerance of 64 species present on the ground or in trees, both in of savanna (cerrado sentido restrito) and semi-deciduous forest areas, and measured the temperature variation in different vertical strata of these two habitats. The results suggest that vegetation type (savanna or forest) affects the heat but not the cold tolerance, whereas the nesting stratum (ground or arboreal) affects both the heat and cold tolerance. Furthermore, I found evidence of a strong phylogenetic signal in the heat and range of thermal tolerances. I also found evidence that savanna ants are more vulnerable to global warming than are ants from the semideciduous forest. Furthermore, in savannas, ground ants seem to be more vulnerable than arboreal ants, while the opposite is true in forests. Secondly, I evaluated if thermal tolerance is a plastic trait among Cerrado ants. For this, I measured the thermal tolerance of habitat generalist species that occurred both in savannas and forests. In addition, I evaluated if the thermal tolerance of species from a given habitat varies seasonally. I found that cold tolerance varies seasonally regardless of the type of vegetation or nesting/foraging stratum where the species occurred. I also found that savanna ants have a greater heat tolerance than those from the forest. Finally, during one year, I performed a carbohydrate and protein supplementation experiment for arboreal ants in order to understand the effects of nutrient availability for these ants. I found that both carbohydrate and protein availability increased the species richness and overall abundance of ants foraging in trees. However, only the supplementation of sugar increased the thermal tolerance and the size of colonies in artificial nests. Trees that received sugar presented lower levels of herbivore damage in their leaves than those from the remaining supplementation treatments. Overall, my study reinforces the idea that climatic variations within and between habitats affect the thermal tolerance of ectothermic organisms, indicating that studies at the local scale are essential to understand the effects of global warming on these organisms.